2013
DOI: 10.1038/nsmb.2676
|View full text |Cite
|
Sign up to set email alerts
|

Divergent evolution of protein conformational dynamics in dihydrofolate reductase

Abstract: Molecular evolution is driven by mutations, which may affect the fitness of an organism and are then subject to natural selection or genetic drift. Analysis of primary protein sequences and tertiary structures has yielded valuable insights into the evolution of protein function, but little is known about evolution of functional mechanisms, protein dynamics and conformational plasticity essential for activity. We characterized the atomic-level motions across divergent members of the dihydrofolate reductase (DHF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
204
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(230 citation statements)
references
References 54 publications
12
204
0
Order By: Relevance
“…In the case of the well-studied EcDHFR, it is known that the enzyme undergoes multiple conformational states of the Met20 loop during the catalytic cycle, corresponding to open, closed and occluded states [32]. For comparison, the authors solved crystal structures of hDHFR at different stages in the catalytic cycle, and demonstrated that, in contrast with EcDHFR, the corresponding loop in hDHFR remains locked in a closed conformation throughout the catalytic cycle [42]. In addition, the authors demonstrated that the active site cleft of hDHFR is more compact than that of EcDHFR when bound to the same ligands, leading the authors to suggest that hDHFR is better pre-organized to facilitate the hydride transfer reaction catalysed by this enzyme.…”
Section: Dihydrofolate Reductasementioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the well-studied EcDHFR, it is known that the enzyme undergoes multiple conformational states of the Met20 loop during the catalytic cycle, corresponding to open, closed and occluded states [32]. For comparison, the authors solved crystal structures of hDHFR at different stages in the catalytic cycle, and demonstrated that, in contrast with EcDHFR, the corresponding loop in hDHFR remains locked in a closed conformation throughout the catalytic cycle [42]. In addition, the authors demonstrated that the active site cleft of hDHFR is more compact than that of EcDHFR when bound to the same ligands, leading the authors to suggest that hDHFR is better pre-organized to facilitate the hydride transfer reaction catalysed by this enzyme.…”
Section: Dihydrofolate Reductasementioning
confidence: 99%
“…Specifically, while the human (hDHFR) and E. coli (EcDHFR) enzymes are structurally highly similar, they have significant differences in their sequences, and the associated reaction kinetics and rate-limiting steps under physiological conditions [44 -46]. Wright and co-workers studied these enzymes using an integrative approach that combined structural biology, mutagenesis, bioinformatics and cell biology techniques, in order to explore the evolutionary implications of the conformational dynamics of the different enzymes in the DHFR enzyme family [42]. In the case of the well-studied EcDHFR, it is known that the enzyme undergoes multiple conformational states of the Met20 loop during the catalytic cycle, corresponding to open, closed and occluded states [32].…”
Section: Dihydrofolate Reductasementioning
confidence: 99%
“…The crystal structure of DHFR coupled with folic acid and NADPH indicates that OG1 of Thr136 is hydrogen bonded to the pteridine moiety of folate through an intervening water molecule (Fig. 1C) (30)(31)(32). OG1 is absent in Ala, so the Thr136Ala mutation is predicted to alter the affinity of DHFR for folic acid and therefore to compromise enzyme function.…”
Section: Resultsmentioning
confidence: 99%
“…The Thr136Ala substitution is predicted to result in reduced affinity of DHFR for its substrate, consistent with our observation that the enzyme activity of recombinant DHFR Ora was blunted. Interestingly, in vitro mutagenesis of Glu30, an amino acid that also forms a hydrogen bond with the pteridine moiety of folate (30,32) and bonds directly to Thr136 (31,32), produced a catalytically inactive form of DHFR (40). The Thr136Ala mutated version of the DHFR protein (DHFR Ora ) was barely detectable in either Ora/Ora mice or 293T cells transfected with a DHFR cDNA encoding the mutated version.…”
Section: Discussionmentioning
confidence: 99%
“…However, a variety of allosteric reactions demonstrate that such a contiguous pathway is not necessary, nor does a net conformational change always occur with agonist binding. To account for these results, it has been suggested that changes in dynamics with allosteric binding are responsible for the changes to substrate binding constants or promoter binding (Bhabha et al 2013;Boehr et al 2013;Gunasekaran et al 2004;Nussinov and Tsai 2013;Tsai et al 2009). Long-range structural vibrations, often referred to as the collective vibrational modes, or global vibrations, readily provide a mechanism to correlate motions between distant regions.…”
Section: Introduction: Long-range Vibrations and Allosterymentioning
confidence: 99%